2016
DOI: 10.1016/j.psyneuen.2016.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent caffeine consumption increases adulthood anxiety-related behavior and modifies neuroendocrine signaling

Abstract: Caffeine is a commonly used psychoactive substance and consumption by children and adolescents continues to rise. Here, we examine the lasting effects of adolescent caffeine consumption on anxiety-related behaviors and several neuroendocrine measures in adulthood. Adolescent male Sprague-Dawley rats consumed caffeine (0.3 g/L) for 28 consecutive days from postnatal day 28 (P28) to P55. Age-matched control rats consumed water. Behavioral testing for anxiety-related behavior began in adulthood (P62) 7 days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 61 publications
(100 reference statements)
4
37
0
4
Order By: Relevance
“…As shown in Fig. 2D, the mice in C and S groups showed similar levels of sensitivity in the baseline, acquisition, extinction, and reinstatement of cocaine CPP in their adulthood [F (3,72) = 0.4544, P = 0.0184].…”
Section: Cocaine Enhanced Anxiety-like and Depression-like Behaviorsmentioning
confidence: 86%
See 1 more Smart Citation
“…As shown in Fig. 2D, the mice in C and S groups showed similar levels of sensitivity in the baseline, acquisition, extinction, and reinstatement of cocaine CPP in their adulthood [F (3,72) = 0.4544, P = 0.0184].…”
Section: Cocaine Enhanced Anxiety-like and Depression-like Behaviorsmentioning
confidence: 86%
“…Adolescents represents more susceptibility to substance use than adults (1) because of their immature brain and high willingness for risk-taking behaviors (2). Early exposure to drugs could result in psychiatric problems that often last for a long time, which even persist into adulthood (3)(4)(5). Our previous study found that adolescent cocaine exposure results in a prolonged modification on synapses in adult medial prefrontal cortex (mPFC) (6).…”
mentioning
confidence: 99%
“…Caffeine is the most commonly used psychostimulant throughout the world (O’Neill, ; Rath, ; Warzak, ). Caffeine consumption has become especially prevalent among adolescents and young adults, with over 75% of this population consuming caffeine daily (James, Kristjansson, & Sigfusdottir, ; National Sleep Foundation, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the neural mechanism of caffeine is well-understood, the conditions under which caffeine improves cognitive and physical performance remain equivocal (6). Low to moderate doses of caffeine improve performance 37 on cognitive tasks (7)(8)(9)(10), yet higher doses may result in decrements in performance and increased negative mood or affects, such as anxiety and jitteriness (8,11). It is unclear if caffeine has primary effects on performance or whether it merely reverses a deficit in performance introduced by caffeine withdrawal (12)(13)(14).…”
mentioning
confidence: 99%